As relações de poder e as disputas simbólicas pelo Guandu em Cachoeiro de Itapemirim (1966-2016) - Rocha, Silvana Maria Gomes da (2017)
The commercial importance of Cachoeiro de Itapemirim, within the twentieth century, played a large role in the formation of a political elite with enough strength to create the first Espírito Santo State Rail Road, while still village, called the Espírito Santo Caravelas Company of Navigation and Rail Road. However, the instillation of the republican regime and the expansion of the railroad network itself; called for much labor which contributed to the creation of Guandu. This neighborhood, Guandu, from their beginning until now, possesses multiple characteristics: some untouched, others altered by the public, which has been a target for citizens and public administration. This process is simply a part of the political clash inherent in different social groups; once in prominence. Especially within the past fifty years, 1966-2016, has determined the urban configuration of Guandu.